Grandmaster of demonic cultivation = Mo dao zu shi. 4 - Moxiangtongxiu (Grandmaster of Demonic Cultivation, 2022)
The Long way home. History stands poised to repeat itself as Wei Wuxian and Lan Wangji are besieged by walking corpses atop the Burial Mounds. It is here fate offers them a second chance to protect their loved ones and unmask the true instigator of this grisly onslaught. As shocking revelations shake the cultivation world to its very core, the unlikely couple becomes preoccupied with other matters--like an evening of drunken impulse that may push their budding relationship into bold new territory. The novel series that inspired the live-action drama, The Untamed!